Adaptive Real-Time Removal of Impulse Noise in Medical Images. - HosseinKhani, Zohreh; Hajabdollahi, Mohsen; Karimi, Nader; Soroushmehr, Reza; Shirani, Shahram; Najarian, Kayvan; Samavi, Shadrokh (Journal of Medical Systems, 2018)
Noise is an important factor that degrades the quality of medical images. Impulse noise is a common noise caused by malfunctioning of sensor elements or errors in the transmission of images. In medical images due to presence of white foreground and black background, many pixels have intensities similar to impulse noise and hence the distinction between noisy and regular pixels is difficult. Therefore, it is important to design a method to accurately remove this type of noise. In addition to the accuracy, the complexity of the method is very important in terms of hardware implementation. In this paper a low complexity de-noising method is proposed that distinguishes between noisy and non-noisy pixels and removes the noise by local analysis of the image blocks. All steps are designed to have low hardware complexity. Simulation results show that in the case of magnetic resonance images, the proposed method removes impulse noise with an acceptable accuracy.